2020
DOI: 10.2147/cmar.s228578
|View full text |Cite
|
Sign up to set email alerts
|

<p>Impact of the Activation Status of the Akt/mTOR Signalling Pathway on the Clinical Behaviour of Synovial Sarcoma: Retrospective Analysis of 174 Patients at a Single Institution</p>

Abstract: Phosphoinositide 3-kinase (PI3K) and the downstream Akt/mammalian target of rapamycin (mTOR) pathway are central to the control of cell proliferation and survival. Although abnormal activation of this pathway has been well established in a variety of tumours, limited studies are available on synovial sarcoma. The aim of this study was to investigate the expression of several key proteins of those pathways in synovial sarcomas and to correlate the expression of these proteins with clinicopathologic features and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Cell cycle and cell adhesion are the basic state of tumor cells, and are closely related to tumor proliferation and metastasis, respectively. High expression of TOR signaling pathway suggested that the sarcoma was highly invasive and significantly correlated with poor prognosis of the sarcoma, which all suggested that it could be used as a targeted therapeutic target for the sarcoma 38 . Targeted regulation of the TOR signaling pathway by drugs can affect the malignant phenotype of sarcomas 39,40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell cycle and cell adhesion are the basic state of tumor cells, and are closely related to tumor proliferation and metastasis, respectively. High expression of TOR signaling pathway suggested that the sarcoma was highly invasive and significantly correlated with poor prognosis of the sarcoma, which all suggested that it could be used as a targeted therapeutic target for the sarcoma 38 . Targeted regulation of the TOR signaling pathway by drugs can affect the malignant phenotype of sarcomas 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…High expression of TOR signaling pathway suggested that the sarcoma was highly invasive and significantly correlated with poor prognosis of the sarcoma, which all suggested that it could be used as a targeted therapeutic target for the sarcoma. 38 Targeted regulation of the TOR signaling pathway by drugs can affect the malignant phenotype of sarcomas. 39,40 NF-κB has been reported as a biomarker for sarcoma treatment efficacy and differentiation.…”
Section: F I G U R E 8 Snorna-genes Co-expression Interaction Network...mentioning
confidence: 99%